2013
DOI: 10.1121/1.4819117
|View full text |Cite
|
Sign up to set email alerts
|

Infrasonic interferometry of stratospherically refracted microbaroms—A numerical study

Abstract: The atmospheric wind and temperature can be estimated through the traveltimes of infrasound between pairs of receivers. The traveltimes can be obtained by infrasonic interferometry. In this study, the theory of infrasonic interferometry is verified and applied to modeled stratospherically refracted waves. Synthetic barograms are generated using a raytracing model and taking into account atmospheric attenuation, geometrical spreading, and phase shifts due to caustics. Two types of source wavelets are implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The method presented here relies on an active source like the volcano used. However, source-independent techniques are being developed based on interferometry of the ambient noise field [Fricke et al, 2013[Fricke et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The method presented here relies on an active source like the volcano used. However, source-independent techniques are being developed based on interferometry of the ambient noise field [Fricke et al, 2013[Fricke et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the detection and localization of underwater explosions, as those monitored with, for example, the IMS, can be enhanced with the inclusion of the infrasonic component [ Prior et al , ]. The question of how underwater sources contribute to the ambient atmospheric noise field also arises, which in turn can be used for imaging of the (upper) atmosphere [ Haney , ; Fricke et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study with direct tropospheric waves measured at two locations, Haney [2009] has shown that interferometry can be applied to infrasonic ambient noise to retrieve temperature and the strength of winds in the troposphere. In our recent paper [Fricke et al, 2013], we applied infrasonic interferometry to synthetically generated microbaroms, which were refracted by the stratosphere to gather insight and prove their feasibility for probing the stratosphere. In a recent approach, Godin et al [2014] were able to use traffic noise to estimate the wind vector in the troposphere, showing that the atmosphere can also be probed by ambient noise.…”
Section: Introductionmentioning
confidence: 99%
“…All Rights Reserved. In our recent paper [Fricke et al, 2013], we applied infrasonic interferometry to synthetically generated microbaroms, which were refracted by the stratosphere to gather insight and prove their feasibility for probing the stratosphere. In a recent approach, Godin et al [2014] were able to use traffic noise to estimate the wind vector in the troposphere, showing that the atmosphere can also be probed by ambient noise.…”
Section: Fricke Et Almentioning
confidence: 99%